2021
DOI: 10.3390/vaccines9121455
|View full text |Cite
|
Sign up to set email alerts
|

Educational Interventions on Pregnancy Vaccinations during Childbirth Classes Improves Vaccine Coverages among Pregnant Women in Palermo’s Province

Abstract: Maternal immunization is considered the best intervention in order to prevent influenza infection of pregnant women and influenza and pertussis infection of newborns. Despite the existing recommendations, vaccination coverage rates in Italy remain very low. Starting from August 2018, maternal immunization against influenza and diphtheria-tetanus-pertussis were strongly recommended by the Italian Ministry of Health. We conducted a cross sectional study to estimate the effectiveness of an educational interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 29 publications
(32 reference statements)
1
46
0
Order By: Relevance
“…Moreover, several studies conducted in Europe confirmed the key role of HCWs in modifying knowledge, personal convictions, and choices about vaccinations among the general population [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, several studies conducted in Europe confirmed the key role of HCWs in modifying knowledge, personal convictions, and choices about vaccinations among the general population [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 91%
“…Another study reported that improving pregnant women’s knowledge about vaccination has helped to increase the acceptance rate of the influenza vaccine [ 60 ]. These findings are attributed to the positive association of knowledge about influenza vaccination with acceptance rate [ 61 , 62 , 63 ]. Healthcare providers play a key role in helping women make an informed choice about vaccines when they are deciding whether to accept the influenza vaccine during pregnancy [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the implementation of vaccination education interventions on maternal immunization during antenatal classes significantly improved adherence to vaccinations during pregnancy. 24 …”
Section: Discussionmentioning
confidence: 99%